Double burden of malnutrition among elderly population of Delhi - Goswami, Anil Kumar; Nongkynrih, Baridalyne; Kalaivani, Mani; Gupta, Sanjeev Kumar; Pandav, Chandrakant S (Indian Journal of Community Health, 2016)
Background: Nutritional status is an important determinant for elderly, directly influencing their susceptibility to diseases, adversely affecting their quality of life. Aim & Objective: To assess the nutritional status of elderly persons aged ?60 years residing in an urban resettlement colony of Delhi. Materials and Methods: A community-based cross-sectional study was conducted in a resettlement colony in Delhi. Cluster random sampling was used. Three out of ten blocks were selected randomly. All elderly persons present in the selected blocks were included. Information on socio-demographic variables was collected. Arm span and weight were measured by trained investigators. Data was entered in MS Excel 2007 and analyzed in Stata 11.0. Multiple logistic regression was done to determine the association between nutritional status and socio-demographic variables Results: A total of 711 elderly persons were recruited. About half (53.2%) had normal nutritional status, 20.8% were underweight and 19.4% were overweight and 6.6% were obese. Under-nutrition was significantly associated with gender, while overweight/obesity was found to be significantly associated with age (p<0.001), gender (p<0.001), occupation (p<0.001) and economic dependency (p< 0.001). Conclusion: Dual burden of malnutrition was seen, so there is a need to promote healthy eating and lifestyle to address both spectrum of malnutrition.